Evaluation of enzymatic proteoglycan loss and collagen degradation in human articular cartilage using ultrashort echo time‐based biomarkers: A feasibility study. (13th December 2021) - Wan, Lidi; Cheng, Xin; Searleman, Adam C.; Ma, Ya‐Jun; Wong, Jonathan H.; Meyer, R. Scott; Du, Jiang; Tang, Guangyu; Chang, Eric Y.
Abstract : The objective of the current study was to investigate the feasibility of quantitative 3D ultrashort echo time (UTE)‐based biomarkers in detecting proteoglycan (PG) loss and collagen degradation in human cartilage. A total of 104 cartilage samples were harvested for a trypsin digestion study (n = 44), and a sequential trypsin and collagenase digestion study (n = 60), respectively. Forty‐four cartilage samples were randomly divided into a trypsin digestion group (tryp group) and a control group (phosphate‐buffered saline [PBS] group) (n = 22 for each group) for the trypsin digestion experiment. The remaining 60 cartilage samples were divided equally into four groups (n = 15 for each group) for sequential trypsin and collagenase digestion, including PBS + Tris (incubated in PBS, then Tris buffer solution), PBS + 30 U col (incubated in PBS, then 30 U/ml collagenase [30 U col] with Tris buffer solution), tryp + 30 U col (incubated in trypsin solution, then 30 U/ml collagenase with Tris buffer solution), and tryp + Tris (incubated in trypsin solution, then Tris buffer solution). The 3D UTE‐based MRI biomarkers included T1, multiecho T2 *, adiabatic T1ρ (AdiabT1ρ ), magnetization transfer ratio (MTR), and modeling of macromolecular proton fraction (MMF). For each cartilage sample, UTE‐based biomarkers (T1, T2 *, AdiabT1ρ, MTR, and MMF) and sample weight were evaluated before and after treatment. PG and hydroxyproline assays were performed. Differences between groups and correlations were assessed. All the evaluated biomarkers were able to differentiate between healthy and degenerated cartilage in the trypsin digestion experiment, but only T1 and AdiabT1ρ were significantly correlated with the PG concentration in the digestion solution ( p  = 0.004 and p  = 0.0001, respectively). In the sequential digestion experiment, no significant differences were found for T1 and AdiabT1ρ values between the PBS + Tris and PBS + 30 U col groups ( p  = 0.627 and p  = 0.877, respectively), but T1 and AdiabT1ρ values increased significantly in the tryp + Tris ( p  = 0.031 and p  = 0.024, respectively) and tryp + 30 U col groups (both p  < 0.0001). Significant decreases in MMF and MTR were found in the tryp + 30 U col group compared with the PBS + Tris group ( p  = 0.002 and p  = 0.001, respectively). It was concluded that AdiabT1ρ and T1 have the potential for detecting PG loss, while MMF and MTR are promising for the detection of collagen degradation in articular cartilage, which could facilitate earlier, noninvasive diagnosis of osteoarthritis. Abstract : Noninvasive detection of PG loss and collagen degradation by imaging would help early‐stage diagnosis. UTE T1 and AdiabT1ρ relaxation times have the potential to detect PG loss, while MTR and MMF are promising biomarkers for detecting collagen degradation in articular cartilage, which could facilitate earlier, noninvasive diagnosis of osteoarthritis. Changes in the quantitative UTE‐based biomarkers, (A) T1, (B) T2 *, (C) AdiabT1ρ, (D) MTR, and (E) MMF, after sequential digestion in four different groups, are shown.